Management of colorectal cancers. Issue 5 (1st October 2004) - Lewis, R; Flynn, A; Dean, M E; Melville, A; Eastwood, A; Booth, A
Abstract : The management of colorectal cancers, published in a recent issue of Effective Health Care, is reviewed.